Pemberian Diet Pasca Bedah pada Pasien Kista Ovarium Pasca Bedah Kistektomi: Laporan Kasus - Faradhila Anindya; Dominikus Raditya Atmaka (Media Gizi Kesmas, 2024)
Background: Ovarian cysts are a condition where there is a lump filled with fluid, pus or solid tissue on the ovary. Based on the Indonesian Health Demographic Survey, the incidence of ovarian cysts in Indonesia reached 37.2% and most often occurs in women aged 20-50 years. Ovarian cysts can be treated with cystectomy surgery. Anemia can occur in ovarian cyst patients either due to genetic history, lifestyle changes or side effects from surgery. The standardized Nutritional Care Process (NCP) is carried out to provide appropriate nutritional care to ovarian cyst patients who will undergo cystectomy surgery. Objectives: To know the implementation of Nutrition Care Process by providing a post-surgical diet for ovarian cyst patients Methods: A case study was conducted in March 2021 on patients at Bakti Dharma Husada Hospital, Surabaya. Sampling has been determined in advance by the hospital nutritionist and internship guide according to the case criteria. The data collection method was carried out with literature studies and analytical observation for 3 days in the field of intake, physical/clinical, biochemical and anthropometric domains. Results: Monitoring and evaluation results showed that there were fluctuating changes in laboratory, physical/clinical results, and patient intake increased within 3 days. The patient's food intake has increased significantly and it has reach the target of at least 70%. Conclusion: The recovery condition is considered quite good based on the results of food intake monitoring, although the intake on the first and second days cannot be categorized as a significant increase because the patient was only given liquid food via a nasogastric tube (NGT). The results of the physical/clinical examination on the second and third days of the patient still felt nauseous, but this condition did not affect overall food intake.